A Comparative Study on the Behavior of Adolescents Raised by Normal Families and Broken Home Families in Keboan Anom Village, Gedangan, Sidoarjo : Studi Komparatif Tentang Perilaku Remaja Yang Diasuh Oleh Keluarga Normal Dan Keluarga Broken Home Di Desa Keboan Anom, Gedangan, Sidoarjo - Anita Tri Maharani Hariyadi; Istikomah Istikomah (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study is (1) to find out the behavior of adolescents who are raised by normal families. (2) knowing the behavior of teenagers who are raised by broken home families and (3) knowing the comparison or differences in the behavior of teenagers who are raised by normal families and broken home families. The research method used a mixed method research or a combination of quantitative and qualitative with a population of 150 teenagers living in RW.03, RW.05 and RW.06 and obtained a sample of 60 teenagers to study. Then the data analysis technique used in the study used the independent sample t-test formula. Based on the research that has been done, the results of the research are as follows: (1) the behavior of adolescents who are cared for by normal families using an average analysis technique that has been through validity and reliability tests gets a score of 3.95 which is in the interval of 3.67 – 5.00 which means that the behavior of adolescents is quite good. (2) and the behavior of adolescents who are cared for by broken home families using an average analysis technique that has been through validity and reliability tests obtains a score of 2.72 which is in the interval 2.34 - 3.66, which means that adolescent behavior is classified as poor. . (3) based on the independent sample t-test test output in the equal variances assumed section, it is known that the value of sig.(2-tailed) is 0.000 <0.05.